Des « arrangements » à la confrontation. Les jeunes coiffeuses et ouvriers du bâtiment face à leur·s employeur·s - Camille Trémeau (La Nouvelle Revue du Travail)
The present contribution takes studies of young hairdressers and construction workers to ascertain to what extent young employees operating in these sectors make full use of the social rights at their disposal. It demonstrates that this is not always the case due to the “professional complicity” that many share with their employers. Having said that, such analysis is also incomplete since it masks the variable and discretionary aspects of many of these arrangements – explaining the need to also consider the conditions in which they occur. For instance, whereas all interviewees found themselves in a subordinate position whilst doing their apprenticeships, their subsequent trajectories could be quite varied, with construction workers more likely to “scream and shout” whereas hairdressers showed a greater tendency to avoid conflict. The end result is to reveal the full range of gendered and otherwise differentiated forms of subordination that feature in these single-sex working environments.